Can we define reliable risk factors for anastomotic strictures following radical prostatectomy?. Issue 4 (November 2020) - Spek, Annabel; Buchner, Alexander; Khury, Farouk; Khoder, Wael; Tritschler, Stefan; Stief, Christian
Background: To identify risk factors for anastomotic strictures in patients after radical prostatectomy. Methods: In all, 140 prostate cancer patients with one or more postoperative anastomotic strictures after radical prostatectomy were included. All patients underwent transurethral anastomotic resection at the University Hospital of Munich between January 2009 and May 2016. Clinical data and follow-up information were retrieved from patients' records. Statistical analysis was done using Kaplan-Meier curves and log rank-test with time to first transurethral anastomotic resection as endpoint, Chi-square-test, and Mann–Whitney-U test. Results: In all, 140 patients with a median age of 67 years (IQR: 61–71 years) underwent radical prostatectomy. Median age at time of transurethral anastomotic resection was 68 years (IQR: 62–72). Patients needed 2 surgical interventions in median (range: 1–15). Median time from radical prostatectomy to transurethral anastomotic resection was 6 months (IQR: 3.9–17.4). Median duration of catheterization after radical prostatectomy was 10 days (IQR: 8–13). In all, 26% (36/140) received additional radiotherapy. Regarding time to first transurethral anastomotic resection, age and longer duration of catheterization after radical prostatectomy with a cutoff of 7 days showed no statistically significant differences (p = 0.392 and p = 0.141, respectively). Tumor stage was no predictor for development of anastomotic strictures (p = 0.892), and neither was prior adjuvant radiation (p = 0.162). Potential risk factors were compared between patients with up to 2 strictures (low-risk) and patients developing > 2 strictures (high-risk): high-risk patients had more often injection of cortisone during surgery (14% vs 0%, p < 0.001) and more frequently advanced tumor stage pT > 2 (54% vs 38%, p = 0.055), respectively. Other risk factors did not show any significant difference compared to number of prior transurethral anastomotic strictures. Conclusions: We could not identify a reliable risk factor to predict development of anastomotic strictures following radical prostatectomy.